Professional Quality of Life Factors and Relationships in Nursing and Psychiatric Nursing Students: An Exploratory Study - Kathryn M. Chachula RN, PhD (SAGE Publishing, 2021)
Introduction Professional quality of life (ProQOL) that encompasses compassion satisfaction (CS) and compassion fatigue (CF) comprised of burnout (BO) and secondary traumatic stress (STS) has been raised as a world-wide issue for the nursing profession. Limited attention has been paid to the vulnerabilities of nursing students to ProQOL and the associated mechanisms. Purpose Determine what factors are predictive of ProQOL in a population of undergraduate nursing and psychiatric nursing students. Methods: A cross-sectional survey was conducted comprised demographic questions and four validated measures: the Professional Quality of Life Scale (version 5), Core Self-Evaluations Scale, Perceived Stress Scale, and Life Events Checklist (version 5). Results Students in long-term care-palliative care rotations reported significantly higher levels of BO in comparison to other care areas. Regression analysis revealed students with low self-efficacy and high perceived stress were predictive of BO. Students with increased exposures to prior traumatizing life events were predictive of STS. Students with high levels of self-efficacy and less intent-to-leave were predictive of having CS. Conclusion Findings assist educators, clinicians, and policy makers in understanding at-risk clinical settings and predictors of ProQOL in pre-licensure students. Curricular recommendations that include mindfulness, coping and crisis peer-debriefing, and emotional intelligence are discussed.